Neoclassical Realist Theory of International Politics - Ripsman, Norrin M. ; Taliaferro, Jeffrey W. and Lobell, Steven E. (New York Oxford University Press, 2016)
"Since Gideon Rose's 1998 review article in the journal World Politics and especially following the release of Lobell, Ripsman, and Taliaferro's 2009 edited volume Neoclassical Realism, the State, and Foreign Policy, neoclassical realism has emerged as major theoretical approach to the study of foreign policy on both sides of the Atlantic. Proponents of neoclassical realism claim that it is the logical extension of
Include Index
Keywords: Realism--Political aspects -- International relations -- International relations--Philosophy